THE SENSITIZING RESPONSE IN IPSILATERAL AND CONTRALATERAL LOWER LIMB STRAIGHT LEG RAISING DURING UPPER LIMB TENSION TEST 2A IN CERVICOBRACHIAL DISORDERS (International Journal of Physiotherapy, 2016)
Background: Neck pain is increasingly becoming a common problem. Cervicobrachial disorder is a dysfunction of nerve root of the cervical spine due to its compression which leads to ischemic changes that cause sensory and motor dysfunction. Many studies has been done on SLR test which affects upper limb sensitizing response by means of doing ipsilateral and bilateral SLR. The study revealed that the abduction ROM for shoulder was greater during contra lateral SLR with ULTT-2a when compared to ipsilateral SLR.Methods: 30 subjects (18 males and 12 females) were included in this study. The ULTT-2a is performed on each subject, following this ipsilateral and contra lateral SLR was performed. The sensitising response perceived by the subjects was recorded. Outcome measures were Range of Motion and sensation description. After the intervention the shoulder abduction and straight leg raising ranges were measured. Analysis was performed using independent t-test.Result: Significant difference was found in shoulder abduction (p< 0.001) and SLR (P< 0.002) but no considerable difference was found on the VAS. (P> 0.11). There was no difference in sensitizing response (Tingling, Burning, Sharp shooting) during ipsilatral and contra lateral straight leg raise.Conclusion: This study concludes that in order to obtain the same sensitizing response during ULTT-2a of contra-lateral SLR as during ULTT-2a of ipsilateral SLR, the angle of SLR and shoulder abduction during ULTT-2a of contra lateral SLR will be greater. This finding will be proved beneficial in the treatment of patients with cervico brachial disorders.